JENIS-JENIS I'LAL DALAM KITAB 'AQDULLUL FI SIROH AL-BATHUL KARYA SAYYID HABIB MUHAMMAD BIN HASAN BIN ALAWIY AL-HADDAD - Witarsih; Yayan Rahtikawati; Muhamad Abdul Halim; Heri Setiawan (Hijai - Journal on Arabic Language and Literature, 2026)
Background: I‘lāl is an important topic in Arabic morphology (ṣarf) that explains changes involving weak letters in Arabic words. This study focuses on ‘Aqdulul fī Sīrah al-Bathūl by Sayyid Habib Muhammad bin Hasan bin Alawiy al-Haddad. Purpose: This study aims to classify i‘lāl based on morphological transformation processes and types of fi‘l mu‘tal. Method: This qualitative study employs a descriptive-analytical method. Data were collected through reading and note-taking techniques and analyzed through description, classification, and interpretation. Results: he analysis identified 189 instances of i‘lāl. Based on transformation processes, the data include i‘lāl bi al-qalb, bi al-naql, bi al-taskīn, bi al-ḥadhf, and several combined forms. Based on fi‘l mu‘tal, the data comprise mithāl, ajwaf, nāqiṣ, lafīf mafrūq, and lafīf maqrūn. Conclusion: The findings demonstrate diverse i‘lāl patterns and provide a systematic description of morphological changes in the text.  Keywords: I‘lāl; Arabic Morphology; Fi‘l Mu‘tal; Morphological Transformation; ‘Aqdulul fī Sīrah al-Bathūl.